Effect of simvastatin on vascular tone in porcine coronary artery: potential role of the mitochondria - Almukhtar, H.; Garle, M.J.; Smith, P.A.; Roberts, Richard E. (Elsevier, 2016)
Statins induce acute vasorelaxation which may contribute to the overall benefits of statins in the treatment of cardiovascular disease. The mechanism underlying this relaxation is unknown. As statins have been shown to alter mitochondrial function, in this study we investigated the role of mitochondria in the relaxation to simvastatin. Relaxation of porcine coronary artery segments by statins was measured using isolated tissue baths. Mitochondrial activity was determined by measuring changes in rhodamine 123 fluorescence. Changes in intracellular calcium levels were determined in freshly isolated smooth muscle cells with Fluo-4 using standard epifluorescent imaging techniques. Simvastatin, but not pravastatin, produced a slow relaxation of the coronary artery, which was independent of the endothelium. The relaxation was attenuated by the mitochondrial complex I inhibitor rotenone (10 μM) and the complex III inhibitor myxothiazol (10 μM), or a combination of the two. The complex III inhibitor antimycin A (10 μM) produced a similar time-dependent relaxation of the porcine coronary artery, which was attenuated by rotenone. Changes in rhodamine 123 fluorescence showed that simvastatin (10 μM) depolarized the membrane potential of mitochondria in both isolated mitochondria and intact blood vessels. Simvastatin and antimycin A both inhibited calcium-induced contractions in isolated blood vessels and calcium influx in smooth muscle cells and this inhibition was prevented by rotenone. In conclusion, simvastatin produces an endothelium-independent relaxation of the porcine coronary artery which is dependent, in part, upon effects on the mitochondria. The effects on the mitochondria may lead to a reduction in calcium influx and hence relaxation of the blood vessel.